The Economic Transition of Health in Africa: A Call for Progressive Pragmatism to Shape the Future of Health Financing. Issue 4 (2nd October 2017) - Ly, Caroline; Eozenou, Patrick; Nandakumar, Allyala; Pablos-Mendez, Ariel; Evans, Timothy; Adeyi, Olusoji
Abstract : Abstract —The new financing landscape for the Sustainable Development Goals has a larger emphasis on domestic resource mobilization. But, given the significant role of donor assistance for health, the fungibility of government health spending, and the downward revision of global growth, this article looks at what is possible with regard to a country's own ability to finance priority health services. Using cross-sectional and longitudinal economic and health spending data, we employ a global multilevel model with regional and country random effects to develop gross domestic product (GDP) projections that inform a dynamic panel data model to forecast health spending. We then assess sub-Saharan African countries' abilities to afford to finance their own essential health needs and find that there are countries that will still rely on high out-of-pocket or donor spending to finance an essential package of health services. To address this, we discuss policy opportunities for each set of countries over the next 15 years. This longer-term view of the economic transition of health in Africa stresses the imperative of engaging policy now to prioritize customized strategies and institutional arrangements to increase domestic financing, improve value for money, and ensure fairer and sustainable health financing. We address the need for rhetoric on UHC to incorporate "progressive pragmatism, " a proactive joint approach by developing country governments and their development partners to ensure that policies designed to achieve universal health coverage align with the economic reality of available domestic and donor financing.